Quantitative proteomic analysis of longissimus dorsi muscle in Chinese and Western pigs using DIA mass spectrometry with PRM validation - Hanyu Cao; Xiaojin Li; Fei Xie; Changsheng Jiang; Mengmeng Jin; Ahmed H. Ghonaim; Man Ren; Qianqian Hu; Shenghe Li (PLoS ONE, 2026)
Huoshou black pig (HS) is a well-known indigenous Chinese breed distinguished by superior meat quality compared to Western breeds. To investigate the molecular mechanisms underlying these differences, we performed Data-Independent Acquisition(DIA) proteomic analysis on the longissimus dorsi (LD) muscle from HS and Yorkshire (YY) pigs. We identified 262 differentially expressed proteins (DEPs), including 134 upregulated and 128 downregulated in HS relative to YY. Functional enrichment analysis revealed that these DEPs were significantly involved in small molecule metabolism, oxidoreductase activity, and several key signaling pathways such as the mTOR, AMPK, and PI3K-Akt pathways. Protein -protein interaction network analysis highlighted roles in structural proteins, glycolysis, and ribosome biogenesis. Integrated transcriptomic and proteomic analysis identified five candidate genes ( MGST2 , PNPO , CALD1 , NCAM1 , ACSS1 ) potentially associated with meat quality traits. Parallel reaction monitoring (PRM) and quantitative PCR (qPCR) validated the consistent differential expression of these genes at both the protein and mRNA levels. These findings provide novel insights into the molecular mechanisms regulating pork quality in indigenous pig breeds.